2018
DOI: 10.1590/1809-4430-eng.agric.v38n3p369-375/2018
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Sorption of Rice in the Husk

Abstract: This study aimed to determine the thermodynamic properties of sorption processes (desorption and adsorption) of rice in the husk, cv. Urucuia. A static-gravimetric method was used to reach equilibrium moisture content at different temperatures (10, 20, 30, 40, and 50 °C ± 1°C) and relative humidity levels (10, 30, 50, 70, and 90 % ± 2%). A decrease in moisture content led to an increment of the integral isosteric heat of sorption, indicating a higher demand for energy to remove moisture from the product. Diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Besides, at higher a w , sites are covered with water molecules, implying in less mobility for the water molecules ( Eim et al., 2011 ); also, ΔS of a material is proportional to the number of available sorption sites at a specific energy level ( Nascimento et al., 2019 ), and as desorption progresses, more sites are exposed and become available. Similar results were found by Zeymer et al. (2018) , in the desorption process of rice, which ΔS values varied from 0.22 to 4.64 kJ/kg.K, for an EMC variation from 21.5 to 2.6 g H 2 O/100 g db.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Besides, at higher a w , sites are covered with water molecules, implying in less mobility for the water molecules ( Eim et al., 2011 ); also, ΔS of a material is proportional to the number of available sorption sites at a specific energy level ( Nascimento et al., 2019 ), and as desorption progresses, more sites are exposed and become available. Similar results were found by Zeymer et al. (2018) , in the desorption process of rice, which ΔS values varied from 0.22 to 4.64 kJ/kg.K, for an EMC variation from 21.5 to 2.6 g H 2 O/100 g db.…”
Section: Resultssupporting
confidence: 88%
“…This behavior is already expected for desorption processes, since it requires the addition of energy to occur (endergonic reaction) ( Oulahna et al., 2012 ). Non-spontaneous desorption processes were also found in rice ( Zeymer et al., 2018 ) and in crambe fruits ( Oliveira et al., 2017 ).
Figure 3 Gibbs free energy for the desorption process of JP (A) and JS (B), at 25 °C (■), 35 °C (●), 45 °C (▲), and 55 °C (◆).
…”
Section: Resultsmentioning
confidence: 94%
“…For the same temperature, with increasing equilibrium moisture content, there is an increase in water activity. Previous research with different agricultural products also reported this behavior (Oliveira et al, 2011;Costa et al, 2015;Zeymer et al, 2018b;Campos et al, 2019). Water activity reports the amount of water molecules available for different reactions in the product, as well as the development of microorganisms; therefore, by increasing the equilibrium moisture content, a greater amount of moisture is available for these reactions, resulting in an increase in water activity (a w ).…”
Section: Resultsmentioning
confidence: 81%
“…Recently, thermodynamic parameters such as enthalpy, entropy, Gibbs free energy and isosteric heat, among others, have been investigated for different types of grains and seeds, such as Opuntia ficus indica seeds (Hassini et al, 2015), Salvia hispanica L. seeds (Velázquez-Gutiérrez et al, 2015), Piper nigrum L. seeds (Yogendrarajah et al, 2015), Tamarindus indica L. seeds (Alpizar-Reys et al, 2017), Beta vulgaris L. seeds (Oliveira et al, 2017), Phaseolus vulgaris L. grains (Miano;Sabadoti;Augusto, 2018), Lactuca sativa L. seeds (Zeymer et al, 2018a), Oryza sativa L. grains (Zeymer et al, 2018b), Helianthus annuus L. seeds (Campos et al, 2019), Triticum vulgare L. grains (Mattioda;Jorge;Jorge, 2019). However, studies involving the thermodynamic properties of moisture sorption of ryegrass seeds have not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have also analyzed the thermodynamic properties viz., heat of sorption, differential molar entropy, properties of sorbed water, spreading pressure, and net integral enthalpy and entropy of the product during the sorption process. These properties hold crucial importance in the assessment of product stability and processing parameters (Mbarek & Mihoubi, 2019; Zeymer, Corrêa, de Oliveira, Baptestini, & Faria, 2018; Zhang et al., 2020). However, the products listed were prepared using either dry blending of the ingredients predetermined proportions or spray‐drying technique.…”
Section: Introductionmentioning
confidence: 99%